(3GdfXGe GdeMGSHj hfXGe eMGSHI GdJcGdja aj GdefTGJ GdNOejI (B"(3GdafGOb(B"s - (3gGTe GMeO(B, (3YWjIs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2002)
(3JLO aj gPG GdcJGH (B: (3YehejGJ fXGe GdeYdheGJ hGdfTGW GdafObj , fXGe GdeYdheGJ NWhGJ GdJUeje , GdNUGFU GdeJejRI ddfJTGW GdafObj ,GdCfTWI hGdhXGFa GdafObjI JUeje GdeLehYGJ GdeSJfOI ef GdfTGW ,GdJShjbGJ GdLQOjI hGdbhGFe GdeGdjI aj GdfTGW GdafObj , fXGe eMGSHI GdJcGdja aj GdfTGW , CSGdjH Jbjje GdCOGA aj GdfTGW GdafObjs
(3GdeQGLY U(B.329s
Keywords: (3GdafGOb(B-(3eMGSHIs